2015
DOI: 10.1177/1098612x15569615
|View full text |Cite
|
Sign up to set email alerts
|

Sampling sites for detection of feline herpesvirus-1, feline calicivirus andChlamydia felisin cats with feline upper respiratory tract disease

Abstract: The oropharynx can be recommended as the preferred single sampling site for the detection of FCV, FHV-1 and C felis if only one sample can be taken; however, taking samples at different sites significantly increases the detection rate for all pathogens studied. Interestingly, sampling from a site with FURTD-associated lesions did not increase the likelihood of detecting the infectious agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 31 publications
4
29
0
Order By: Relevance
“…Previous studies have shown that oropharyngeal samples could be ideal to obtain DNA for FHV-1 and RNA for FCV and respiratory pathogens. 30,31 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that oropharyngeal samples could be ideal to obtain DNA for FHV-1 and RNA for FCV and respiratory pathogens. 30,31 …”
Section: Discussionmentioning
confidence: 99%
“…Chlamydia felis ( C . felis ) is another known pathogen that is frequently detected in cats with FURTD and has been observed in the nose of cats with FURTD [59]. Notably in this study, C .…”
Section: Discussionmentioning
confidence: 71%
“…This statement applies more to feline herpesvirus because cats with feline herpesvirus shed virus transiently rather than continuously in contrast to feline calicivirus (24,25). The single sampling site that was chosen could have distorted the results; it would have been better to take a sample also from the oropharynx to increase the detection rate for the two pathogens (26). Bacterial osteomyelitis in young children occurs most commonly in the metaphyses because the blood vessels trap bacterial emboli (27).…”
Section: Discussionmentioning
confidence: 99%
“…Performing cytology and culture could have helped in ruling out an infectious agent. Blood culture should be recommended in animals with systemic disease (26). In the two cats, because their clinical signs were mild and there was no fever, blood culture was not considered to be indicated.…”
Section: Discussionmentioning
confidence: 99%